2011
DOI: 10.1007/s11182-011-9552-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heat treatment on mechanisms of martensitic transformations in ferromagnetic Ni49Fe18Ga27Co6 single crystals

Abstract: Ferromagnetic alloys based on Ni-Fe-Ga-(Сo) undergo thermoelastic В2(L2 1 )-10М-14М-L1 0 martensitic transformations (MTs) and are capable of reversible changes in size and shape when subjected to thermal action, mechanical stresses and magnetic fields. The Ni-Fe-Ga-(Сo) alloys possess reserve plasticity unlike the brittle Ni 2 MnGa alloys, and can be used in a variety of current technological applications [1]. The authors of [2,3] investigated the magnetic properties and characteristic temperatures of thermoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…As shown previously, these particles allow for modifying the properties of the alloy, i.e. not only the strength but also the phase transformation temperatures and the transformation hysteresis properties are affected [9].…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…As shown previously, these particles allow for modifying the properties of the alloy, i.e. not only the strength but also the phase transformation temperatures and the transformation hysteresis properties are affected [9].…”
Section: Resultsmentioning
confidence: 88%
“…2). Related transmission electron microscopy (TEM) studies have shown [9] that in these single crystals a bimodal microstructure is formed. In addition to the large γ-phase particles, small γ′-phase particles with a size of 10-30 nm are precipitated (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stepped heat treatments of as-grown Ni 49 Fe 18 Ga 27 Co 6 single crystals were conducted to achieve a high level of austenite strength properties and maintaining plasticity: 1) high-temperature annealing at 1373 K for 25 min, followed by quenching in water to increase the crystal plasticity through the precipitation of large γ-phase particles (disordered fcc structure) [15]; 2) lowtemperature ageing at 673 K for 1 h (type-II) and at 823 K for 0.5 h, (type-III) followed by cooling in air to result in precipitation of γ'-phase particles, allowing control of the characteristic temperatures of MT and functional properties of crystals [15].…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the stress hysteresis with increasing temperature at T > 473 K can be connected with the generation of defects and increasing diffusive mobility of defects at the stress-induced MT. The reduction of stress hysteresis at T > 530 K in NiFeGa and at T > 630 K in NiFeGaCo can be connected with ageing processes, which take place in these crystals [88,97]. However additional investigations are necessary to understand the physical reasons for the non-monotonic temperature dependence of the stress hysteresis at temperatures over 473 K.…”
Section: Thermoelastic Stress-induced Intermartensitic Transformation...mentioning
confidence: 99%